Audit Recommendations and Management Auditing: A Case Study and Some Remarks - Churchill, Neil C. (Journal of Accounting Research, 1966)
Neil C. Churchill, Audit Recommendations and Management Auditing: A Case Study and Some Remarks, Journal of Accounting Research, Vol. 4, Empirical Research in Accounting: Selected Studies 1966 (1966), pp. 128-151